Wirusocentryczne narracje reporterskie z nurtu „mrocznej biologii” - Izabella Adamczewska-Baranowska (Zagadnienia Rodzajów Literackich)
This paper discuses an eco-apocalyptic non-fiction, which can be described as dark biology (referring to dark fantasy, dark science-fiction or noir crime fiction). The analysis is focused on Richard Preston’s, David Quamenn’s, Karl Taro Freenfeld’s and Nathan Wolfe’s medical/scientific nonfiction and heroic-exploratory narratives. The authors of dark narratives about viruses use the motives typical of crime, thriller, horror or sensation fiction. This analysis is set in a context of „dark ecology” — Timothy Morton’s eco-critical project.